2016
DOI: 10.3389/fncel.2016.00147
|View full text |Cite
|
Sign up to set email alerts
|

E2 Regulates Epigenetic Signature on Neuroglobin Enhancer-Promoter in Neuronal Cells

Abstract: Estrogens are neuroprotective factors in several neurological diseases. Neuroglobin (NGB) is one of the estrogen target genes involved in neuroprotection, but little is known about its transcriptional regulation. Estrogen genomic pathway in gene expression regulation is mediated by estrogen receptors (ERα and ERβ) that bind to specific regulatory genomic regions. We focused our attention on 17β-estradiol (E2)-induced NGB expression in human differentiated neuronal cell lines (SK-N-BE and NT-2). Previously, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Administration of 17β-estradiol (E2) was also reported to upregulate Ngb levels in mouse hippocampal neurons and primary cortical astrocytes [ 221 , 222 ]. Interestingly, whereas no estrogen response element is found within the Ngb promoter, Guglielmotto and colleagues demonstrated that E2 induces the recruitment of estrogen receptor alpha (ERα) to the first intron of Ngb that acts as an enhancer element, which in turn induces chromatin remodeling and leads to enhanced Ngb expression [ 223 ]. In a model of brain-induced ischemia in gerbils, administration of recombinant human neuronal erythropoietin resulted in Ngb upregulation and reduced neuronal death [ 224 ].…”
Section: Neuroglobinmentioning
confidence: 99%
“…Administration of 17β-estradiol (E2) was also reported to upregulate Ngb levels in mouse hippocampal neurons and primary cortical astrocytes [ 221 , 222 ]. Interestingly, whereas no estrogen response element is found within the Ngb promoter, Guglielmotto and colleagues demonstrated that E2 induces the recruitment of estrogen receptor alpha (ERα) to the first intron of Ngb that acts as an enhancer element, which in turn induces chromatin remodeling and leads to enhanced Ngb expression [ 223 ]. In a model of brain-induced ischemia in gerbils, administration of recombinant human neuronal erythropoietin resulted in Ngb upregulation and reduced neuronal death [ 224 ].…”
Section: Neuroglobinmentioning
confidence: 99%
“…ERα regulates neuroglobin expression through genomic transcript region regulation (Guglielmotto et al, 2016 ). Estradiol is capable of upregulating neuroglobin through activation of ERß (De Marinis et al, 2013 ; Fiocchetti et al, 2015 ).…”
Section: Cytoarchitecture-specific Mechanism Involved In Sexual Diffementioning
confidence: 99%
“…A previous study evaluated Ngb expression in astrocytes after brain trauma and reported that Ngb expression is present in subacute and chronic injuries but not acute trauma ( 28 ). Moreover, in other studies, it was found that Ngb is expressed in microglia and astrocytes specifically during conditions such as traumatic brain injury ( 84 , 122 ) and that estradiol regulates the expression of Ngb in astrocytes ( 66 ) through the estrogen receptor β (ERβ) ( 22 ), while ERα is involved in the regulation of Ngb in neurons ( 137 ). Interestingly, tibolone, a synthetic hormone with estrogenic, progestogenic, and androgenic actions, has also been reported to induce Ngb expression in astrocytic-like cells in vitro under glucose deprivation ( 65 ) (Figure 1 ).…”
Section: Neuroglobin Expression In Astrocytesmentioning
confidence: 99%